Aplikasi Sistem Informasi Praktikum pada Program Studi Informatika Universitas Kristen Petra Berbasis Website - Cynthia Budiono; Lily Puspa Dewi; Alexander Setiawan (Jurnal Infra, 2022)
Presently, Petra Christian University informatics study program use SAOCP for laboratory activities problems. But there are drawbacks that can be minimized. Recruitment, assessments, attendance using Microsoft Excel for every data collection carried out. The person in charge of the practicum schedule often experiences confusion in setting the schedule. The current system also reads the NRP by using the old NRP format which is start with M alphabet. Based on these problems, it is necessary to have an application that can answer problems in the informatics study program. This system is created using PHP with the CodeIgniter 3 framework as the main basis, and SQL for the database. In this information system, the user has six different types of access right, namely admin, lecturer, head of the laboratory, permanent assistant, lecturer assistant, and student. The final result of this application is the integration of information such as vacancies, ratings, attendance, and reports. Based on the results of the existing questionnaire, 100% of the correspondents considered that the features made in this application were sufficient in accordance with the needs of the company.